Fenomena Cinta Lesbian - Susanti, Anita; Widjanarko, Mochamad (Jurnal Psikologi, 2015)
The aims of this research is to describe the love phenomenon of lesbians in the Kudus Regency. The subjects were three lesbian individuals living in Kudus. The research method was phenomenology which based on the subjective experience or phenomenological experience. The data collecting techniques were observation and interview. This study applied snowball sampling technique, meaning that the sample was carried out serially by asking information from previously interviewed subject. The data analysis method was matrix by Miles & Hubberman consisting of three stages of simultanious activities, they were: data reduction, data presentation and conclusion or verification. The result shows that two lesbians have experiencedÂ  lesbian love previously but one subject has experienced lesbian love for the first time. There are intimacy, passion and commitment in lesbian love. There is conflict in their relationship but there is also hope for their future lesbian love relationship.